Ukrainian versions of the Composite Scale of Morningness and Munich Chronotype Questionnaire. Issue 6 (3rd June 2022) - Senyk, Oksana; Jankowski, Konrad S.; Cholii, Sofiia
ABSTRACT: Chronotype is an individual characteristic that can be important for health and quality of life. There are currently no instruments to measure chronotype in Ukrainians, so this study was conducted to provide adaptations of questionnaires with proven psychometric properties. The Composite Scale of Morningness (CSM) and the Munich ChronoType Questionnaire (MCTQ) were translated into Ukrainian using the parallel blind method; 776 Ukrainians then completed the questionnaires and answered questions on demographics and substance use. The Ukrainian version of the CSM showed high internal consistency (Cronbach's alpha = 0.874). Greater morningness (CSM) correlated with earlier midsleep on sleep-corrected free days (MSFsc), r = −0.623. Later chronotypes as derived from both CSM and MCTQ exhibited more pronounced social jetlag and greater consumption of stimulants. In accordance with the assumptions underlying the CSM, confirmatory factor analysis proved the one-factor structure of the Ukrainian version of the questionnaire. The cut-off scores (bottom/top 10%) for the Ukrainian CSM were 23 or less for evening types and 42 or more for morning types. The Ukrainian CSM and MCTQ appear to be psychometrically sound measures of chronotype ready for use in future studies.